Three things I learn at sleep-time: children's accounts of sleep and rest in their early childhood education programs. Issue 5 (20th October 2021) - Gehret, Hannah; Cooke, Emma; Staton, Sally; Irvine, Susan; Thorpe, Karen
ABSTRACT: The international quality-improvement agenda for Early Childhood Education (ECE) directs attention to maximising children's learning experiences. Yet routines, and particularly those relating to sleep-rest provision, are not well conceptualised as learning opportunities. Often children who no longer sleep in the daytime are required to lie down without alternative activity. Educator discourse frames these practices as 'teaching self-regulation', yet these experiences afford little opportunity for child-directed learning, and both observational and cortisol studies suggest the potential for negative learning experiences. Prior studies have examined children's emotional response and identified sleep-rest time as disliked, but have not examined children's accounts of learning. In this study, we analyse accounts of learning from 54 children (mean age = 56 months). Collectively, the children identified three learnings. Most children learned that adults regulate sleep-rest opportunities through instruction, reward, punishment and priveledge. Some children reported learning coping strategies including imagination and subversion. A rare few identitfied learning to self-regulate. The findings identify a discrepancy between policy aspiration and educator intent, that foreground self-regulation and the de facto lessons children draw from their sleep-rest experiences. Our findings identify standard sleep-rest provision as sub-optimal and the imperative to view care routines, such as sleep-rest, as opportunities for learning.